2021
DOI: 10.1159/000516504
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac EUS-B-Guided FNA for Diagnosing Cardiac Tumors

Abstract: Primary cardiac tumors are extremely rare. Obtaining a tissue diagnosis is difficult and commonly requires open-heart surgery with associated morbidity. Esophageal endoscopic ultrasound (EUS) and EUS with the EBUS scope (EUS-B) provide real-time sampling of centrally located lung tumors and mediastinal lymph nodes. They also provide an excellent view of the left atrium, since it is located adjacent to the esophagus. To date, left atrium tumor diagnostics by endosonography is poorly explored. We describe 2 exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Moreover, two case reports of Endoscopic ultrasound with bronchoscope-guided fine-needle aspiration (EUS-B-FNA) of left atrial masses has been successfully performed in which cardiac surgery was hazardous due to the comorbidity or previous surgical interventions. The cytopathology confirmed the diagnosis of a Burkitt lymphoma and a synovial sarcoma [33].…”
Section: Eus-guided Cardiovascular Interventionsmentioning
confidence: 54%
“…Moreover, two case reports of Endoscopic ultrasound with bronchoscope-guided fine-needle aspiration (EUS-B-FNA) of left atrial masses has been successfully performed in which cardiac surgery was hazardous due to the comorbidity or previous surgical interventions. The cytopathology confirmed the diagnosis of a Burkitt lymphoma and a synovial sarcoma [33].…”
Section: Eus-guided Cardiovascular Interventionsmentioning
confidence: 54%
“…However, in patients with poor clinical conditions, endosonography could represent a minimally invasive technique to perform a diagnosis, seeing that it provides an excellent view of the left atrium. Two cases of EUS-B-FNA of left atrial masses have been reported with high accuracy and no adverse events [91].…”
Section: Pleural and Cardiac Lesionsmentioning
confidence: 99%
“…While a percutaneous needle biopsy could have been performed to confirm left atrial invasion, EUS‐B‐FNA allowed for minimally invasive and simultaneous diagnosis and evaluation of the degree of invasion by echocardiography, which resulted in prompt initiation of chemotherapy. Thus, EUS‐B‐FNA may be useful for evaluating and diagnosing tumours with cardiac invasion 2 …”
Section: Clinical Imagementioning
confidence: 99%